First record of the symbiotic crab Harrovia elegans De Man, 1887 from west coast of India - Pradip Kachhiya; Piyush Vadher; Imtiyaz Beleem (Journal of Fisheries, 2025)
The present study documents the first record of the crinoid-associated brachyuran crab Harrovia elegans De Man, 1887 from dense beds of the feather star Tropiometra carinata (Lamarck, 1816) in tide pools within the intertidal zone of the Simbor Coast, Gujarat, India. Previously, H. elegans has been reported with different crinoid species from limited localities in Indian waters, including Tamil Nadu and the Andaman and Nicobar Islands, typically at depths ranging from 5 to 200 meters. This report provides detailed morphological descriptions of H. elegans, along with information on its habitat preferences and regional distribution.